Minang Tribe Merchant Family Communication in Shaping Children's Entrepreneurial Behavior - Yan Hendra; Rudianto Rudianto; Leylia Khairani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This research is motivated by facts that prove the success of the Minang tribe in building and developing entrepreneurship from generation to generation. The purpose of this study is to explain family communication in shaping children's entrepreneurial behavior. The research method used is a case study. The research data was obtained through interviews with resource persons, namely the son of a successful entrepreneur in the city of Tebingtinggi. The results showed that family communication in shaping children's entrepreneurial behavior through mechanisms, processes and forms of communication that occur in the family. The formation of children's entrepreneurial behavior occurs along with the passage of four communication functions in the family which include the functions of socializing, educating, motivating and inheriting socio-cultural values that are internalized in children.